The Effect of E-Service Quality and Brand Trust Towards Repurchase Intentions For Cabaco Product on Tokopedia E-Commerce - Gunawan, Geraldo; Rachmawati, Mariana (Journal of Accounting and Finance Management, 2025)
This study aims to analyze the relationship between Tokopedia E-Commerce, E-Service Quality, and Brand Trust as it pertains to the repurchase intentions of Cabaco products. Using the customer as an observational unit, this study aims to examine Cabaco Products at Tokopedia E-Commerce. This study used the multiple linear regression hypothesis test as its research technique for descriptive verification. Studies pertaining to methods of gathering information via surveys, library research, and fieldwork. One hundred fifty people participated in the survey. According to the results, the quality of an e-service and the confidence consumers have in a brand affect their propensity to make a repeat purchase.